Practices for Embedding an Interpretive Qualitative Approach Within a Randomized Clinical Trial. (July 2013) - Plano Clark, Vicki L.; Schumacher, Karen; West, Claudia; Edrington, Janet; Dunn, Laura B.; Harzstark, Andrea; Melisko, Michelle; Rabow, Michael W.; Swift, Patrick S.; Miaskowski, Christine
The embedded approach is a mixed methods design that is most commonly used when qualitative methods are embedded within intervention designs such as randomized clinical trials (RCTs). Scholars have noted challenges associated with embedded procedures and expressed concern that embedded designs undervalue and underutilize interpretive qualitative approaches. This article examines these issues in the context of a study about cancer pain management where qualitative methods were embedded within an RCT design. We describe our practices for stating embedded research questions, designing embedded qualitative data collection within the constraints of the RCT, and developing enriched understandings of the RCT through an interpretive qualitative analysis. These practices provide guidance for intervention researchers planning to embed qualitative components within RCT designs.